Hubungan Pemberian Zink dengan Hitung Limfosit dan Lama Rawat Inap pada Anak dengan Infeksi Virus Dengue di RSUD Dr. Moewardi Surakarta - Panggabean, Imelda (Jurnal Kedokteran Indonesia, 2011)
Background: In theory, lymphocyte count increases in pediatric patients with dengue virus infection,because this infection increases apoptosis process and activation of T lymphocyte function, Th1 cytokineproduction, and B lymphocytes. Administration of zinc is hypothsized to affect immunity changes asshown by these biomarkers. This study aimed to examine the effect of zinc on lymphocyte count andlength of stay in pediatric patients with dengue virus infection.Methods: This study was a randomized controlled trial. A sample of 78 pediatric inpatients withdengue virus infection was selected for study at Dr. Moewardi Hospital Surakarta, between October2010 and March 2011. This sample was divided into 2 groups, consisting of 39 children receivingstandard therapy plus zinc and 39 children receiving standard therapy alone. The dependent variablesunder study were lymphocyte count and length of stay (days) The independent variable wasadministration of zinc. The mean difference in lymphocyte count and length of stay between the twogroups was tested by independent t, using SPSS version 17.0.Results: No statistically significant difference in means was shown of lympocyte count between thetwo groups (p=0.313), meaning that there is no association between administration of zinc andlymphocyte count. In contrast, there was statistically significant difference in means of length of stay(days) between the two groups (p=0.006). Patients receiving zinc had 0.62 days shorter length of staythan those without zinc.Conclusion: Administration of zinc is associated with shortening of length of stay but not associatedwith lymphocyte count.Keywords: children, dengue infection, zinc, lymphocyte, length of stay